2019
DOI: 10.3917/spub.194.0553
|View full text |Cite
|
Sign up to set email alerts
|

Facteurs liés au signalement des évènements indésirables associés aux soins dans un hôpital tunisien

Abstract: La reproduction ou représentation de cet article, notamment par photocopie, n'est autorisée que dans les limites des conditions générales d'utilisation du site ou, le cas échéant, des conditions générales de la licence souscrite par votre établissement. Toute autre reproduction ou représentation, en tout ou partie, sous quelque forme et de quelque manière que ce soit, est interdite sauf accord préalable et écrit de l'éditeur, en dehors des cas prévus par la législation en vigueur en France. Il est précisé que … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…More than half of the articles (45/65, 69.2%) were cross-sectional studies [ 13 , 14 , 16 19 , 21 24 , 26 39 , 41 , 42 , 44 , 45 , 47 51 , 54 – 56 , 59 61 , 64 , 65 , 69 71 , 74 ], 21.5% did not indicate the design type used [ 20 , 25 , 52 , 57 , 58 , 62 , 63 , 66 68 , 72 , 73 , 75 , 76 ], 4.6% were case-control studies [ 40 , 46 , 77 ] (during the same period, the cases had reported ADR and the controls had not), 3.1% (2/65) were mixed studies [ 15 , 43 ] (only data from the quantitative part were used), and one (1.5%) was an intervention study [ 53 ] (pre-intervention data were extracted). Two studies were conducted before a pharmacovigilance system was in place [ 17 , 31 ].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…More than half of the articles (45/65, 69.2%) were cross-sectional studies [ 13 , 14 , 16 19 , 21 24 , 26 39 , 41 , 42 , 44 , 45 , 47 51 , 54 – 56 , 59 61 , 64 , 65 , 69 71 , 74 ], 21.5% did not indicate the design type used [ 20 , 25 , 52 , 57 , 58 , 62 , 63 , 66 68 , 72 , 73 , 75 , 76 ], 4.6% were case-control studies [ 40 , 46 , 77 ] (during the same period, the cases had reported ADR and the controls had not), 3.1% (2/65) were mixed studies [ 15 , 43 ] (only data from the quantitative part were used), and one (1.5%) was an intervention study [ 53 ] (pre-intervention data were extracted). Two studies were conducted before a pharmacovigilance system was in place [ 17 , 31 ].…”
Section: Resultsmentioning
confidence: 99%
“…According to geographical distribution, we located studies carried out in 36 countries: 38.5% were carried out in Asia [ 19 , 22 , 28 , 29 , 31 , 32 , 35 , 37 39 , 44 , 46 , 47 , 50 53 , 56 , 58 , 59 , 61 , 63 65 , 72 ], 27.7% in Africa [ 13 15 , 17 , 18 , 23 , 27 , 30 , 34 , 42 , 45 , 48 , 49 , 65 , 69 71 , 74 ], 24.6% in Europe [ 20 , 21 , 24 , 25 , 33 , 40 , 43 , 54 , 55 , 57 , 60 , 62 , 66 , 73 , 75 , 77 ], 7.7% in America [ 16 , 36 , 41 , 67 , 76 ], and one in Australia [ 27 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations